Morphogenetic implications of peristaltic fluid–tissue dynamics in the embryonic lung. (7th October 2015) - Bokka, Kishore K.; Jesudason, Edwin C.; Warburton, David; Lubkin, Sharon R.
Abstract: Peristalsis begins in the lung as soon as the smooth muscle forms, and persists until birth. Since the prenatal lung is liquid-filled, smooth muscle action can deform tissues and transport fluid far from the immediately adjacent tissues. Stretching of embryonic tissues and sensation of internal fluid flows have been shown to have potent morphogenetic effects. We hypothesize that these effects are at work in lung morphogenesis. To place that hypothesis in a quantitative framework, we analyze a model of the fluid–structure interactions between embryonic tissues and lumen fluid resulting from peristaltic waves that partially occlude the airway. We find that if the airway is closed, deformations are synchronized; by contrast, if the trachea is open, maximal occlusion precedes maximal pressure. We perform a parametric analysis of how occlusion, stretch, and flow depend on tissue stiffnesses, smooth muscle force, tissue shape and size, and fluid viscosity. We find that most of these relationships are governed by simple ratios. Graphical abstract: Highlights: Peristalsis in the prenatal airway critically modulates development. We developed a model of peristaltic fluid–tissue interactions in embryonic lung. Peristalsis flattens cells in the airway tip and elongates cells in the tubule stalk. Occlusion and most measures of stretch depend linearly on smooth muscle force.